2016
DOI: 10.1166/jnn.2016.10901
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Nanohexaconazole on Nitrogen Fixing Blue Green Algae and Bacteria

Abstract: Nanohexaconazole is a highly efficient fungicide against Rhizoctonia solani. Nanoparticles are alleged to adversely affect the non-target organisms. In order to evaluate such concern, the present study was carried out to investigate the effect of nanohexaconazole and its commercial formulation on sensitive nitrogen fixing blue green algae (BGA) and bacteria. Various activities of algae and bacteria namely growth, N-fixation, N-assimilation, Indole acetic acid (IAA) production and phosphate solubilization were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…The enhanced bioactivity of nanoproducts can be attributed to their superior inhibition 31 of the target enzyme in comparison to the conventional counterparts. This nanofungicide did not have any negative impact 14,63,70 on soil health, soil nitrifiers, and nitrogen fixers.…”
Section: ■ Results and Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…The enhanced bioactivity of nanoproducts can be attributed to their superior inhibition 31 of the target enzyme in comparison to the conventional counterparts. This nanofungicide did not have any negative impact 14,63,70 on soil health, soil nitrifiers, and nitrogen fixers.…”
Section: ■ Results and Discussionmentioning
confidence: 88%
“…To determine the antifungal potential of these imidazole medicines and the benefits associated with nanotechnological interventions, the present research was undertaken to develop nanoformulations of clotrimazole, econazole nitrate, and miconazole nitrate for the management of harmful phytopathogens, R. solani, S.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to affecting photosynthesis, MNMs would affect the algal nitrogen fixation ability (Cherchi and Gu, 2010;Kumar et al, 2016). After exposure to nano-TiO 2 , both the occurrence and intracellular levels of the nitrogen-rich cyanophycin grana proteins (CGPs) in cyanobacteria Anabaena variabilis increased with the increasing concentration and time of nano-TiO 2 exposure, indicating inhabitation in nitrogen fixation activity (Cherchi and Gu, 2010).…”
Section: Mnms Affect Algae's Photosynthesis and Nitrogen Fixationmentioning
confidence: 99%
“…After exposure to nano-TiO 2 , both the occurrence and intracellular levels of the nitrogen-rich cyanophycin grana proteins (CGPs) in cyanobacteria Anabaena variabilis increased with the increasing concentration and time of nano-TiO 2 exposure, indicating inhabitation in nitrogen fixation activity (Cherchi and Gu, 2010). Likewise, it was reported that nano-hexaconazole, a nanoscale polymer carrier for pesticides, caused inhibition in blue-green algae's activity of nitrogen assimilating enzymes (Kumar et al, 2016).…”
Section: Mnms Affect Algae's Photosynthesis and Nitrogen Fixationmentioning
confidence: 99%
“…Characteristic feature of this developed formulation is biosafety aspect, and after application of nano-hexaconazole, no impact was observed on soil nitrifiers such as blue green algae and cynobacteria species. Therefore, nano-formulations maintain the sustainable soil fertility and productivity compared with conventional formulations [35].…”
Section: Nanoemulsion Formulationmentioning
confidence: 99%